2019
DOI: 10.1177/0961463x18820736
|View full text |Cite
|
Sign up to set email alerts
|

When less time is preferred: An analysis of the conceptualization and measurement of overemployment

Abstract: Socioeconomic panel data indicate that numerous employees would prefer to work less, i.e. that they are overemployed. However, due to inconsistent definitions and divergent operationalizations of overemployment, integrating existing research results is challenging and implications for research and practice are difficult to draw. To advance research in this field, we present an analysis of the concept and measurement of overemployment. To analyze the concept, we proceed in two steps. In step 1, we present the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Indeed, although work is increasingly appreciated, and particularly among young people in post-industrial societies, as a means to develop personal tastes, and less and less in relation to dimensions linked to achievement and certain social and moral duties, such as various studies have shown ( Cogin, 2012 ; Lloyd, 2012 ; Valenzuela et al, 2015 ; Samuel and Kanji, 2019 ; Balderson et al, 2020 ), for a large part of the youth, and specifically for those from Braga that we have surveyed, who mostly have precarious jobs, or who have the prospect of having them, work cannot be perceived as the expression of personal tastes and vocations. The meaning of work refers, as has been said, increasingly to instrumental aspects, such as salary and stability, which make it possible to have enough money to dedicate to other spheres of life ( Figure 5 ), and particularly to those of leisure and consumption, which appears as an important facet of the identity of these young people ( Figure 11 ), just as happens with other youth in European post-industrial societies ( Cogin, 2012 ; Durán Vázquez and Duque, 2018 ; Hiemer and Andresen, 2019 ). If the job satisfies any of these aspirations, young people may feel more or less satisfied with the job they do ( Tables 1 , 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, although work is increasingly appreciated, and particularly among young people in post-industrial societies, as a means to develop personal tastes, and less and less in relation to dimensions linked to achievement and certain social and moral duties, such as various studies have shown ( Cogin, 2012 ; Lloyd, 2012 ; Valenzuela et al, 2015 ; Samuel and Kanji, 2019 ; Balderson et al, 2020 ), for a large part of the youth, and specifically for those from Braga that we have surveyed, who mostly have precarious jobs, or who have the prospect of having them, work cannot be perceived as the expression of personal tastes and vocations. The meaning of work refers, as has been said, increasingly to instrumental aspects, such as salary and stability, which make it possible to have enough money to dedicate to other spheres of life ( Figure 5 ), and particularly to those of leisure and consumption, which appears as an important facet of the identity of these young people ( Figure 11 ), just as happens with other youth in European post-industrial societies ( Cogin, 2012 ; Durán Vázquez and Duque, 2018 ; Hiemer and Andresen, 2019 ). If the job satisfies any of these aspirations, young people may feel more or less satisfied with the job they do ( Tables 1 , 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…All this shows that work is no longer such a fundamental part of personal identity, as it had been for youth in other times (Durán Vázquez and Duque, 2018). Precisely for this reason, some young people prefer to work fewer hours, freeing up the remaining time for other activities that have equal or more meaning for them (Eurofound, 2017;Hiemer and Andresen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…With a few exceptions (De Moortel et al, 2018; Van Emmerik and Sanders, 2005 in their sensitivity analyses), overemployment is mostly operationalised as the difference between actual working hours and preferred working hours per week (e.g. Bartoll and Ramos, 2020; Hiemer and Andresen, 2020; Lee et al, 2015; Wang and Reid, 2015; Zimmert and Weber, 2021). This operationalisation is debatable, for three main reasons.…”
Section: Methodsmentioning
confidence: 99%
“…However, overemployment as a preference to work fewer hours is related to the employee's income and status. A reduction in working hours has risks, such as loss of status and income (Hiemer & Andresen, 2019). Thus, despite the part-time preference, men who work part-time will not perceive the job as better quality than a full-time job.…”
Section: Theoretical Implicationsmentioning
confidence: 99%